DAMPAK KUALITAS AIR TANAH TERHADAP KUALITAS TANAMAN TOMAT CHERRY (SOLANUM L. VAR CERASIFORME) - Diatara, Shinta Atilia; Nurpilihan, Nurpilihan (Universitas Medan Area, 2019)
Irrigation is important for plants so that if irrigation water needs are not met it can affect plant growth and development, irrigation water used in this study is ground water. Substitution of fertilizers using nutrient solutions becomes a solution so that the nutrient requirements in hydroponic cultivation are met. Mixing water and nutrients along with irrigation is known as fertigation. Fertigation using autopot that is self watering fertigation can make efficient use of water because it does not require electricity and pumps but gives good results. The purpose of this study was to determine the effect of groundwater quality impacts on the quality of cherry tomato plants. The research method used is descriptive method. The quality parameters of cherry tomatoes used in this study are total dissolved solids, hardness, vitamin C, water content, fat content, protein content, carbohydrate content and ash content. The results of research on ground water quality indicate that the quality of ground water used has good quality. The results showed the quality of cherry tomatoes with the value of each parameter that is the total value of dissolved solids of fruit (ºbrix) 10; the value of fruit hardness (gForce) 2618.95 and; levels of vitamin C (mg / 100g) fruit 25.16; fruit ash content (%) 1.00; fruit protein content (%) 2.18; fruit fat content (%) 0.26; carbohydrate content of fruit (%) 6.01 and; fruit moisture content (%) 90.55. The results of groundwater quality and cherry tomato quality indicate that ground water affects the quality results of cherry tomato plants..